Persistence of Novel First-Line Antiretroviral Regimes in a Cohort of HIV-Positive Subjects, Coris 2008–2010. Issue 2 (February 2013) - Jarrin, Inma; Hernández-Novoa, Beatriz; Alejos, Belén; Riera, Melchor; Navarro, Gemma; Bernardino, Jose Ignacio; Rivero, Maria; del Amo, Julia; Moreno, Santiago; ,
Background: The aim of this study was to estimate the persistence of the most commonly used first-line combined antiretroviral regimens (cART) in HIV-infected adults in the CoRIS cohort. Methods: CoRIS is an open prospective multicentre cohort of HIV-infected adults naive to cART at entry. Patients enrolled between January 2008 and June 2010 were included. The main outcome was treatment persistence, defined as time from cART initiation to first treatment change (TC). Cox models taking into account competing risks to estimate sub-hazard ratios (sHR) were performed. Results: Of 1, 512 patients, 919 (60.8%) initiated cART with the backbone tenofovir disoproxil fumarate (TDF) plus emtricitabine (FTC) plus efavirenz (EFV), 252 (16.7%) plus lopinavir/ritonavir (LPV/r), 129 (8.5%) plus atazanavir/ritonavir (ATV/r), 110 (7.3%) plus darunavir/ritonavir (DRV/r) and 102 (6.7%) plus nevirapine (NVP). Among 414 patients who switched therapy, reason for switching was available for 393. The most frequent reasons were toxicity (40%), simplification (14%) and treatment failure/resistance (13%). In multivariate analyses, there were significant differences in the risk of TC according to initial cART regimen ( P <0.001). Initiating TDF plus FTC with NVP (sHR 1.94, 95% CI 1.38, 2.72) or LPV/r (sHR 1.89, 95% CI 1.45, 2.47) was associated with higher risk of TC than initiating with TDF plus FTC plus EFV. No differences in TC were found between initiating EFV versus ATV/r (sHR 1.29, 95% CI 0.89, 1.86) or DRV/r (sHR 0.98, 95% CI 0.59, 1.65) with TDF plus FTC as backbone. Conclusions: Switching from initial cART regimens is frequent, toxicity being the main reason for it. The significantly greater persistence of some combinations may be useful for making decisions when initiating cART.